RANCANG BANGUN SISTEM INFORMASI MONITORING DAN EVALUASI PELAYANAN PELANGGAN PADA PARAMUDA TOUR & TRANSPORT - Archam Ali Bachtiar; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Paramuda Tour & Transport is praying The Companies Engaged on Field Travel Bureau. Paramuda Tour & Transport has experienced a decline in the last three years. In the year 2013 period 541 customers down 6 % in 2014 to 508 customers. Then down again 18.7 % in 2015 to 413 customers. With total decrease 24.7 % of subscribers in 2013 until 2015 resulted in the company argo has a tendency to decrease. It is because the singer company are not know advantages disadvantages the given service is shown to the customer.In order to overcome problems related to the created information system monitoring and evaluation of customer service . Created a system that includes customer tour management, monitoring and evaluation services, managing customer complaints.The test results showed the information system of monitoring and evaluation of customer service can help determine the service needs to be improved and the service needs to be maintained. In addition to the provision of online reports, the company can easily access and obtain information through a questionnaire evaluation report, report customer complaints, reports the characteristics of the customer, and the customer tour reports.